Studi Aktivitas Antibakteri Ekstrak Etanol Daun Stroberi (Fragaria x ananassa (Weston) Rozier) Terhadap Bakteri Propionibacterium acnes - Mandike Ginting; Pricella Ginting; Sinta Apriliana Sari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Strawberry leaves (Fragaria x ananassa (Westo) Rozier) contain tannin, flavonoids; secondary metabolites which have antibacterial properties, whereby the flavonoids can disrupt the function of the bacterial cell wall, while the tannins can inhibit microbial extracellular enzymes. Method; Experimental research with the maceration method using 70% ethanol. The ethanol extract of strawberry leaves (Fragaria x ananassa (Weston) Rozier) was used in this study, and it was tested for the simple characteristic test, the phytochemical screening test, and the antibacterial activity test using the disc diffusion method with sample concentrations of 10%, 12%, and 14%. Results; The results obtained from the simplicial characteristic test showed that the simplicial met the requirements for the water content test, water-soluble essence test, ethanol-soluble extract content test, total ash content test, and acid-soluble ash content test. The phytochemical screening showed that strawberry leaves contained alkaloids, flavonoids, tannins, and saponins. The antibacterial activity test showed that the ethanol extract of strawberry leaves (Fragaria x ananassa (Weston) Rozier) had an inhibitory effect on the growth of Propionibacterium acnes bacteria with an extract concentration of 10%, 12%, and 14% showing a diameter of inhibition zone of 17.3 mm respectively, 17.78 mm and 19.08 mm. Conclusion; The results of the research on the optimal concentration of the ethanol extract of Strawberry leaves (Fragaria x ananassa (Weston) Rozier) against Propionibacterium acnes bacteria at a concentration of 14% resulted in a diameter of 19.08 mm inhibition zone, this antibacterial activity is in a strong category.